2008
DOI: 10.1021/ic800568k
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Timescale Photoreactivity of a Model Compound Related to the Active Site of [FeFe]-Hydrogenase

Abstract: Ultraviolet (UV) photolysis of (mu-S(CH 2) 3S)Fe 2(CO) 6 ( 1), a model compound of the Fe-hydrogenase enzyme system, has been carried out. When ultrafast UV-pump infrared (IR)-probe spectroscopy, steady-state Fourier transform IR spectroscopic methods, and density functional theory simulations are employed, it has been determined that irradiation of 1 in an alkane solution at 350 nm leads to the formation of two isomers of the 16-electron complex (mu-S(CH 2) 3S)Fe 2(CO) 5 within 50 ps with evidence of a weakly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
89
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(109 citation statements)
references
References 13 publications
20
89
0
Order By: Relevance
“…These included species arising from CO-loss, which would be expected to be present based on previous studies of the photochemistry of hydrogenase sub-site analogues and is further indicated by the similar dynamics for the TRIR peak recovery reported above to previous work on similar systems. [20][21][22][23][24][25] Ground state carbonyl ligand dissociation energies were calculated to be 40, 47 and 57 kcal/mol for the CO ap , CO eq and CO dppv ligands respectively, in reasonably good agreement with the TD-DFT results reported previously (45, 51 and 58 kcal/mol, respectively). 14 It is noteworthy that the available photon energies at 335, 490 and 572 nm are 85, 58 and 50 kcal/mol, respectively, suggesting that, even at the longest wavelength studied, CO dissociation is by no means prohibited, though it may be approaching the limit at which it is possible for the CO dppv ligand at longer wavelengths.…”
Section: Dft Calculations Of Photoproduct Speciessupporting
confidence: 80%
See 3 more Smart Citations
“…These included species arising from CO-loss, which would be expected to be present based on previous studies of the photochemistry of hydrogenase sub-site analogues and is further indicated by the similar dynamics for the TRIR peak recovery reported above to previous work on similar systems. [20][21][22][23][24][25] Ground state carbonyl ligand dissociation energies were calculated to be 40, 47 and 57 kcal/mol for the CO ap , CO eq and CO dppv ligands respectively, in reasonably good agreement with the TD-DFT results reported previously (45, 51 and 58 kcal/mol, respectively). 14 It is noteworthy that the available photon energies at 335, 490 and 572 nm are 85, 58 and 50 kcal/mol, respectively, suggesting that, even at the longest wavelength studied, CO dissociation is by no means prohibited, though it may be approaching the limit at which it is possible for the CO dppv ligand at longer wavelengths.…”
Section: Dft Calculations Of Photoproduct Speciessupporting
confidence: 80%
“…[15][16][17][18][19] Studies of the photochemistry of hydrogenase-based biomimetic compounds are limited and tend toward excitation at wavelengths shorter than 400 nm but, in all of these cases, carbonyl ligand photolysis has been a predominant outcome and it has also been a feature of longer wavelength studies. [20][21][22][23][24][25] It is therefore imperative that experimental verification of predictions suggesting that CO photolysis is expected only to be a minor product of 1 excitation is obtained. In order to understand the intimate processes underpinning the photochemistry of this system, we report timeresolved infrared (TRIR) spectroscopy of 1 following photoexcitation at three different pump wavelengths pump = 335, 490 and 572 nm, resonant with three absorption bands in the UV/Vis spectrum (Fig.…”
Section: Supporting Information Placeholdermentioning
confidence: 99%
See 2 more Smart Citations
“…57 TR-IR spectroscopy of (µ-propanedithiolate)Fe 2 (CO) 6 (see Fig 5 for structure) following <350 nm excitation demonstrated that CO photodissociation was the main photochemical pathway observed, though the photoproduct spectra produced were found to be complex and assignment to a specific photoproduct or to a mixture was not possible, with density functional theory simulations suggesting more than one species could be present. 59 T-2D-IR spectroscopy was employed to unravel the spectroscopy subsequent to photodissociation. Once again, the experiments were performed in the pseudo 3 rd order limit in order to reveal the 2D-IR spectrum of the photoproduct species.…”
Section: T-2d-ir Spectroscopy Of Short-lived Inorganic Photoproductsmentioning
confidence: 99%